A comparative N-of-1 study trial of aspirin Vs clopidogrel in the treatment of peripheral artery disease – A case report (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
N-of-1 or single subject clinical trials consider an individual patient as the sole unit of observation in a study investigating the efficacy or side-effect profiles of different interventions. Aim and objective: The main aim of the study is to compare the efficiency of 2 antiplatelet drugs, Aspirin 81 mg (drug-A) and Clopidogrel 75 mg (drug-B), as N-of-1 trial in the treatment of peripheral artery disease. Method: Single patient N-of-1 Trial. A 4week study period was selected for each drug therapy, in order to allow each treatment an adequate time to manifest its clinical effects. A washout period of 1 week was used between the two drug therapies to eliminate or reduce the carryover effect of the treatment used in the previous time period. Results: The study shows that Clopidogrel (drug-B) was found clinically effective than aspirin in peripheral artery disease. Discussion: Clopidogrel (Drug-B) directly inhibits platelet adhesion, whereas aspirin inhibits only secondary activation of platelets. Conclusion: It was found that Clopidogrel (drug-B) treatment has potent efficiency in patients with symptomatic peripheral artery disease in compared with aspirin in preventing ischemic events.